Kajian Hukum Putusan Hakim atas Pertanggung Jawaban Tindak Pidana Pelaku Pemalsuan Uang Rupiah Perspektif Kriminologi. Studi Kasus: Putusan Nomor : 319/Pid.B/2023/Pn Rap - Suhaiy Batul Aslamiyah Nst , Risdalina Siregar , Kusno (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the criminal liability of perpetrators of Rupiah counterfeiting in Decision Number 319/Pid.B/2023/PN Rap through a normative legal approach and a criminological perspective. The results indicate that the panel of judges correctly applied Article 36 paragraph (1) of Law Number 7 of 2011 in conjunction with Article 55 of the Criminal Code, by proving the fulfillment of the elements of the act, fault, and participation. The sentencing considerations reflect the balance between legal certainty and substantive justice, taking into account the defendant's role and economic motives. Operationally, it is necessary to strengthen law enforcement coordination, optimize counterfeit money detection technology, and improve public financial literacy to prevent similar crimes.